Kinetics of lipase-catalysed functionalisation of epsilon-caprolactone monomer and oligomer with methyl-dglucopyranoside / Muhammad Naziz Saat - Muhammad Naziz , Saat (2019)
One-pot synthesis of oligomeric sugar ester was carried out by lipase-catalysed esterification of -caprolactone (ECL) with methyl-D-glucopyranoside (MGP) followed by chain elongation of ECL monomer/oligomer. Functionalisation was performed in a custom-fabricated glass reactor equipped with Rushton turbine impeller using tertbutanol as reaction medium. Two-level half-fractional factorial design was employed to analyse the effects of selected operating variables namely lipase (1.2-2.8 % w/v), initial ɛ-caprolactone (3.8-11.5 % w/v), initial methyl-D-glucopyranoside (0.04-0.14 % w/v), temperature (40-60 °C) and agitation rate (90-180 rpm) as a function of maximum dry weight (% w/v) of MGP-functionalised ECL oligomer (MGP-6-O-oligo-ECL). It was found that individual variables viz. lipase (XLip), initial -caprolactone (XECL) and temperature (XTemp) significantly affect the maximum product formation (p < 0.05). Twoway interaction effects between variables viz. lipase with initial ECL (XLip XECL), lipase with temperature (XLip XTemp), initial ECL with initial MGP (XECL XMGP), and initial ECL with temperature (XECL XTemp) were found to be significant (p < 0.05) on the final dry weight of functionalised oligomer. Significant two-way interaction between variables suggested the presence of confounding effect among the variables studied. From descriptive statistic of the half-fractional factorial model, the percentage of variation (R2) of the regression model was observed at 99.8 %, which indicated good fitting between predicted and actual data. The model validation using residual analysis showed the variation among predicted and experimental data was normally distributed. From the output of response optimizer program, the best conditions for maximum functionalised oligomer production are as follows: lipase loading of (2.8 % w/v), initial ECL (11.46 % w/v), initial MGP (0.04 % w/v), temperature (60.0 °C), and agitation rate (90 rpm). The proposed mechanism for the functionalisation includes MGP esterification of ECL monomer/oligomer followed by chain elongation with free 6-hydroxyhexanoate monomer units, and both steps are catalysed by lipase. A ping-pong bi-bi mechanism without ternary complex was proposed for esterification of ECL with MGP with apparent values of kinetic constants namely maximal velocity (Vmax), Michaelis constant for MGP (KmMGP) and Michaelis constant for ECL (KmECL) at 3.848 × 10-3 M h-1, 8.189 × 10-2 M and 6.050 M, respectively. Chain propagation step of MGP-functionalised ECL oligomer exhibits the behavior of living polymerization mechanism. The apparent rate constant (rApp) of chain elongation showed highest value when ECL concentration was increased. Synthesized functionalised oligomer showed narrow range of molecular weight from 1,400 to 1,600 (g mol-1) with more than 90 % ECL conversion achieved. Spectroscopic data established the presence of covalent bonding between terminal hydroxyl group in MGP and terminal carboxyl end group of ECL monomer/oligomer. Thermal analysis indicated three degradation stages of functionalised oligomer as compared to two stages of degradation in neat ECL oligomer. The current study highlighted significant potential for enzyme-mediated, one-pot synthetic process in the production of carbohydratefunctionalised bio-oligomer with controllable molecular weight as platform chemicals.